Evaluating Service Quality at Malaysian Public Universities: Perspective of International Students by World Geographical Regions - Wan Salmuni Wan Mustaffa; Rafiduraida Abdul Rahman; Hariyaty Ab Wahid; Siti Asma' Mohd Rosdi@Rodhi; Mohammad Khairi Othman (International Journal of Supply Chain Management, 2019)
Recently, the issue of international students’ perceptions on service quality offered by Malaysian public universities has been debated among practitioners and academicians. The international students may experience different educational services in the host country compared to their home country due to cultural and values differences. In addition, the existing research has reported that the perceptions of international students towards services at Malaysian public universities are only at moderate level. Thus, the aim of this research is to determine the perceptions of international students towards service quality at Malaysian public universities according to world geographical regions, namely Asia, Middle East, and Africa. This research was conducted at Malaysian public universities. An online questionnaire was utilized as a research instrument. The stratified sampling technique was applied to gather the data among international students. The descriptive and one-way ANOVA techniques were performed to analyze the data. Based on the mean results, the Asian students were more satisfied with service offered by Malaysian public universities. The one-way ANOVA analysis result revealed the perceptions of international students towards service quality experienced at Malaysian public universities is significantly different across Asia, Middle East, and Africa regions. This research has an important implication for practitioners. Knowledge concerning the concept of service quality will assist practitioners to manage the service delivery at Malaysian public universities from the international students’ perspectives.